2016
DOI: 10.1186/s12877-016-0329-8
|View full text |Cite
|
Sign up to set email alerts
|

Frailty and post-operative outcomes in older surgical patients: a systematic review

Abstract: BackgroundAs the population ages, increasing numbers of older adults are undergoing surgery. Frailty is prevalent in older adults and may be a better predictor of post-operative morbidity and mortality than chronological age. The aim of this review was to examine the impact of frailty on adverse outcomes in the ‘older old’ and ‘oldest old’ surgical patients.MethodsA systematic review was undertaken. Electronic databases from 2010 to 2015 were searched to identify articles which evaluated the relationship betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
510
5
16

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 799 publications
(596 citation statements)
references
References 41 publications
14
510
5
16
Order By: Relevance
“…These findings were noted, "irrespective of the type of surgery conducted "and were consistent across different frailty measurement techniques [47]. Currently, the literature investigating frailty and surgery has defined 'geriatric' as those above 60 or 65 years old, and studies in this patient population have recognized frailty being more prevalent with increasing age.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…These findings were noted, "irrespective of the type of surgery conducted "and were consistent across different frailty measurement techniques [47]. Currently, the literature investigating frailty and surgery has defined 'geriatric' as those above 60 or 65 years old, and studies in this patient population have recognized frailty being more prevalent with increasing age.…”
Section: Discussionsupporting
confidence: 54%
“…A recent systematic study by Lin et al [47] reported that "in patients over 75 years of age, frailty was associated with increased mortality, post-operative complications, prolonged length of stay and discharge to long term care facility. " These findings were noted, "irrespective of the type of surgery conducted "and were consistent across different frailty measurement techniques [47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,11 This biologic syndrome, which results in decreased resistance to stressors and increased vulnerability to morbidity, has been termed frailty. 12 Multiple frailty indices have been developed to scale a patient's AD and predict their operative risk.…”
Section: Introductionmentioning
confidence: 99%
“…13 These scores have consistently been confirmed as independent risk factors for predicting adverse outcomes for surgical patients across a range of specialties including vascular surgery. 10,11,[14][15][16] Both the modified frailty index (mFI), an 11-point index developed in the American College of Surgeon National Surgical Quality Improvement Program (NSQIP) database, and the Risk Analysis Index (RAI), a simplified version of the Porock 6-month mortality index, have been validated in CEA patients in these national data sets demonstrating that an increasing number of AD is associated with increased 30-day adverse events after CEA including stroke, mortality, and length of stay. 11,17,18 The major limitation of the existing analyses using the mFI and RAI is the use of national data sets which specifically lack long-term follow-up data.…”
Section: Introductionmentioning
confidence: 99%